Factors influencing instrumental activities of daily living (IADL) disability among elderly attending health clinics in Kelantan - Nur Raihan Ismail; Anees Abdul Hamid; Asrenee Ab Razak; Noor Aman Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Instrumental activities of daily living (IADL) is a construct that describes the functional ability to perform complex activities, requiring physical and mental capability that allows an elderly to live independently. Studies on IADL in Malaysia are still lacking. Thus, this study aimed to determine the factors influencing IADL disability among the elderly attending health clinics in Kelantan. A cross-sectional study was conducted using a guided questionnaire consisting of sociodemographic characteristics, health-related conditions, Lawton IADL scale, Elderly Cognitive Assessment Questionnaire (ECAQ), Geriatric Depression Scale (GDS), and Duke Social Support Index (DSSI). Multiple logistic regression (MLR) was performed to assess factors influencing IADL disability. Disabled IADL status was defined as having difficulty performing at least one out of eight activities on the Lawton IADL scale. A sample of 248 elderly from 12 health clinics in Kelantan was included, 36.3% of them had disabled IADL status. In the final MLR model, factors influencing IADL disability were, age group 70 years old and above (Adj. OR 3.52; 95% CI: 1.85, 6.69, p-value<0.001), being unmarried/single (Adj. OR 2.37; 95% CI: 1.25, 4.49, p-value=0.008), no formal education (Adj. OR 4.03; 95% CI: 1.64, 9.88, p-value=0.002), low level of income (Adj. OR 2.37; 95% CI: 1.11, 5.07, p-value=0.026) and those who reported fair or poor self-rated health status (Adj. OR 2.53; 95% CI: 1.31, 4.89, p-value=0.006). Therefore, recognition of these factors is critical to promote a better health policy and to provide appropriate care for the elderly in the country.